Controlling the Seedbeds of Tuberculosis: Diagnosis and Treatment of Tuberculosis Infection - Rangaka, Molebogeng X. (Lancet, 2015)
The billions of people with latent tuberculosis infection serve as the seedbeds for future cases of active tuberculosis. Virtually all episodes of tuberculosis disease are preceded by a period of asymptomatic Mycobacterium tuberculosis infection; therefore, identifying infected individuals most likely to progress to disease and treating such subclinical infections to prevent future disease provides a critical opportunity to interrupt tuberculosis transmission and reduce the global burden of tuberculosis disease. Programs focusing on single strategies rather than comprehensive programs that deliver an integrated arsenal for tuberculosis control may continue to struggle. Tuberculosis preventive therapy is a poorly utilized tool that is essential for controlling the reservoirs of disease that drive the current epidemic. Comprehensive control strategies that combine preventive therapy for the most high-risk populations and communities with improved case-finding and treatment, control of transmission and health systems strengthening could ultimately lead to worldwide tuberculosis elimination. This paper outlines challenges to implementation of preventive therapy and provides pragmatic suggestions for overcoming them. It further advocates for tuberculosis preventive therapy as the core of a renewed global focus to implement a comprehensive epidemic control strategy that would reduce new tuberculosis cases to elimination targets. This strategy would be underpinned by accelerated research to further understand the biology of subclinical tuberculosis infections, develop novel diagnostics, and drug regimens specifically for subclinical tuberculosis infection, strengthen health systems, community engagement, and enhance sustainable large scale implementation of preventive therapy programs.